Advances in Electronic Packaging, Parts A, B, and C 2005
DOI: 10.1115/ipack2005-73288
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Actuators for Low-Form-Factor Electronics Cooling

Abstract: The cooling performance of piezoelectric actuators is evaluated for low-form-factor electronics in this work. A piezoelectric actuator is a cantilever made from metal or plastic with a piezoelectric material bonded to it. Under an alternating electrical current, the piezo actuator oscillates back and forth, generating airflow. Compared to conventional fans, these actuators have the advantages of low power consumption, low noise, and smaller dimensions. The parameters investigated in the experiments are actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The entire setup was placed inside a significantly sized enclosure so as to eradicate any atmospheric and stray fluctuations in the test section region. ) were calculated for the various tested fan/fin geometries according to equations (7), (8) and (9) respectively. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire setup was placed inside a significantly sized enclosure so as to eradicate any atmospheric and stray fluctuations in the test section region. ) were calculated for the various tested fan/fin geometries according to equations (7), (8) and (9) respectively. …”
Section: Methodsmentioning
confidence: 99%
“…% Inc h ) exceeding 375% and 444% respectively relative to a purely natural convection state (Fan off) is achievable on a vertical flat surface. Acikalin et al [8] performed additional comparative studies between an oscillating piezoelectric fan and two commercially available axial fans. Results indicate that piezoelectric fans outperform axial fans both in terms of power consumption (31mW vs. 500mW) as well as cooling volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar study using single piezofan, Acikalin et al [9] obtained significant localized cooling and more than 100% enhancement in convective heat transfer coefficient relative to natural convection. In their extension work [10], it was shown that for a given power consumption piezofans were significantly better than axial fans, and compared to natural convection heat sink the piezofans used lesser volume. Yoo et al [11] attempted the possibility of replacing rotary fan by piezofan.…”
Section: Introductionmentioning
confidence: 98%
“…However, little work has been done to date on the development of forced convection cooling schemes at scales appropriate to handheld devices. Some studies have addressed piezoelectric based fans [9,10], but their low flow rate combined with the requirement for high voltages makes them unlikely competitors in the portable electronics market place. Recently, studies addressing the aerodynamics effects of geometrical scaling in both axial fans [11] and radial fans [12], has lead to the development of low profile rotary fans for potential use in electronics cooling applications.…”
Section: Introductionmentioning
confidence: 99%